SUPER PAPER: Fermented Paper Using Spirogyra sp. Extract Added by Banana Fiber - Hadiatullah, Hadiatullah; Sukmadewi, Desak K.T.; Anggraeni, Ayu Arsyi; Nikmah, Isna Arafatun; Dwiprasetiani, Ririn; Suharjono, Suharjono (Proceeding International Conference on Global Resource Conservation, 2015)
The worlds paper production increased on average 3.05% per year, and this induce an increasing wood demand which causes environmental impact such as deforestation and global warming. The objective of the research is to determine an effect of banana fiber adding into fermented paper product. The method includes bacterial cellulose production, an assay ofÂ  effect of banana pulp adding to fermented paper product continued by characteristics assay include grammage, water absorption, thickness, tensile strength, density, and organoleptic of paper. Data obtained from any parameters analyzed by using One Way Analysis of Variance (ANOVA) with three replications, significantly different results analyzed by multiple analysis of variance Tukey test at Î± â¤ 0.05 using the GENSTAT Discovery Edition 4 program. The addition of different carbon sources affect the production wehreas the addition of 7.5% glucose and 0.75% urea as additional carbon and nitrogen source obtained a thicker and weigher of nata de Spirogyra than control treatment. Variations in the concentration of banana fiber affectÂ  paper characteristics as a showed that fermented paper treated by 75% banana fiber concentrationÂ  had thickness (0.23 mm), weight (0.023 g), grammage (230 g/m2), density (931.325 g/m3), water absorption (0.016) and tensile strength (57,7) and it has closed to be art paper carton. Fermented paper treated by 25% and 50% of banana pulp had grammage of 240 g/m2 and 160 g/m2 which were respectively closed to magazine and matt paper. The addition of banana fiber concentration can optimize the quality of paper optimally.Keywords: Banana fiber; cellulose; fermented paper; grammage